Optimal consumption and portfolio choice with ambiguous interest rates and volatility - Qian Lin; Frank Riedel (Economic Theory, 2020)
We study continuous-time consumption and portfolio choice in the presence of Knightian uncertainty about interest rates. We develop the stochastic model that involves singular priors and analyze optimal behavior. When there is sufficiently large uncertainty about interest rates, the agent invests in the asset market only and abstains from the bond market.
Keywords: D81; G11; G12; 330; Portfolio Choice; Knightian Uncertainty; Model uncertainty; Interest Rate Ambiguity